2013
DOI: 10.1242/jcs.109447
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive systems at the cadherin–F-actin interface

Abstract: SummaryCells integrate biochemical and mechanical information to function within multicellular tissue. Within developing and remodeling tissues, mechanical forces contain instructive information that governs important cellular processes that include stem cell maintenance, differentiation and growth. Although the principles of signal transduction (protein phosphorylation, allosteric regulation of enzymatic activity and binding sites) are the same for biochemical and mechanical-induced signaling, the first step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
193
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(199 citation statements)
references
References 129 publications
(165 reference statements)
5
193
1
Order By: Relevance
“…4 Although the cadherin-catenin complex is commonly described as the 'core' VE-cadherin complex, many other proteins can associate, such as scaffolding proteins and cytoskeletal regulators. 3,5 Some of these proteins, including vinculin, [6][7][8][9][10][11] epithelial protein lost in neoplasm (EPLIN) 12,13 a-actinin 14 and afadin, 15,16 have been found to bind to both a-catenin and actin and are therefore suggested to act as a link between the cadherin-catenin complex and actin. However, biochemical studies showed that a minimal cadherin-catenin complex consisting of E-cadherin, b-catenin and aE-catenin can directly bind to filamentous actin (F-actin).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Although the cadherin-catenin complex is commonly described as the 'core' VE-cadherin complex, many other proteins can associate, such as scaffolding proteins and cytoskeletal regulators. 3,5 Some of these proteins, including vinculin, [6][7][8][9][10][11] epithelial protein lost in neoplasm (EPLIN) 12,13 a-actinin 14 and afadin, 15,16 have been found to bind to both a-catenin and actin and are therefore suggested to act as a link between the cadherin-catenin complex and actin. However, biochemical studies showed that a minimal cadherin-catenin complex consisting of E-cadherin, b-catenin and aE-catenin can directly bind to filamentous actin (F-actin).…”
Section: Introductionmentioning
confidence: 99%
“…To discriminate between the distinct junction morphologies, we will refer to these junctions as focal adherens junctions (FAJs). 3,11 Regulation of actin dynamics during endothelial cell-cell junction remodeling Many kinds of dynamic actin-based structures and organizations exist, depending on the proteins that bind to it. 28 Endothelial cells use distinct actin-based structures at different stages during the process of cell-cell junction formation, maintenance and remodeling, as was described in detail by Hoelzle and colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…Sensing and transmitting forces depend to a large extent on tight interactions between cell adhesion complexes and the cytoskeleton. Mechanosensing and mechanotransduction can be defined as cellular processes that convert mechanical cues into intracellular signaling (Furuse et al 2002;Huveneers and de Rooij 2013;Janmey et al 2013). These processes are exemplified by epithelia that line organ and body surfaces to provide structural support and serve as barriers against diverse external stressors such as mechanical force, pathogens, toxins, and dehydration.…”
mentioning
confidence: 99%
“…Recent data indicate that mechanosensor proteins can undergo force-induced conformational changes that, in turn, induce changes in their activity or affinity for binding partners (Yonemura et al 2010;Huveneers and de Rooij 2013). This can finally lead to the activation of chemical signaling cascades.…”
mentioning
confidence: 99%
See 1 more Smart Citation